Accessible Congregations Campaign: Follow-Up Survey of Impact on Individuals With Intellectual/Developmental Disabilities (ID/DD) - Amado, Angela R. Novak (Journal of religion, disability & health, 2012)
The National Organization on Disability's Accessible Congregations Campaign (ACC) was a national effort in the United States to increase congregational inclusion of people with disabilities. This study's intention was to determine the specific impact of this campaign on the inclusion of people with intellectual/developmental disabilities, to gather information about congregation members’ perspectives on these efforts, and to identify barriers. A random sample of participating congregations was surveyed. Responses indicated that although most congregations had joined the ACC to increase physical accessibility, most benefits of the program and to congregation members were reported in the arenas of increased acceptance, knowledge, and relationship/emotional ties.